Aborsi dalam Perspektif Mahasiswa Kedokteran - Herlina, Lenny; Paris, Ilman; Zahrani, Azisyah Zuleyka; Ilham, Muhammad Luthfi Alan; Almujahid, Sa’id Amir (AS-SABIQUN, 2025)
This study aims to examine and analyze medical students’ perspectives on abortion from multiple dimensions, including religion, health, and legal regulations. A qualitative method was employed, involving 55 medical students from the 2024 cohort at the University of Mataram as respondents. Data were collected through Likert-scale questionnaires to measure levels of agreement with abortion-related statements, as well as open-ended questions for in-depth analysis. The results show that the majority of respondents support abortion only in cases of medical emergencies that threaten the mother’s safety, while rejecting abortion on economic grounds. Reproductive health education was perceived as effective in preventing unethical abortion practices, while Indonesia’s abortion regulations were generally considered fair, though subject to varying interpretations. The findings also indicate that religion significantly influences decision-making, though the extent of its influence differs across individuals. Key factors considered by students in evaluating abortion include medical, economic, psychological, legal, and religious aspects. The study concludes that a holistic approach is essential in addressing abortion issues, balancing medical, social, and ethical dimensions to support health policies that are responsive, inclusive, and respectful of societal values.